The Piks allele of the NLR immune receptor Pik breaks the recognition of AvrPik effectors of the rice blast fungus - Xiao, Gui; Wang, Wenjuan; Liu, Muxing; Li, Ya; Liu, Jianbin; Franceschetti, Marina; Yi, Zhaofeng; Zhu, Xiaoyuan; Zhang, Zhengguang; Lu, Guodong; Banfield, Mark J.; Wu, Jun; et al. (Wiley, 2023)
Arms race co‐evolution of plant–pathogen interactions evolved sophisticated recognition mechanisms between host immune receptors and pathogen effectors. Different allelic haplotypes of an immune receptor in the host mount distinct recognition against sequence or non‐sequence related effectors in pathogens. We report the molecular characterization of the Piks allele of the rice immune receptor Pik against rice blast pathogen, which requires two head‐to‐head arrayed nucleotide‐binding sites and leucine‐rich repeat proteins. Like other Pik alleles, both Piks‐1 and Piks‐2 are necessary and sufficient for mediating resistance. However, unlike other Pik alleles, Piks does not recognize any known AvrPik variants of Magnaporthe oryzae. Sequence analysis of the genome of an avirulent isolate V86010 further revealed that its cognate avirulence (Avr) gene most likely has no significant sequence similarity to known AvrPik variants. Piks‐1 and Pikm‐1 have only two amino acid differences within the integrated heavy metal‐associated (HMA) domain. Pikm‐HMA interacts with AvrPik‐A, ‐D, and ‐E in vitro and in vivo, whereas Piks‐HMA does not bind any AvrPik variants. Characterization of two amino acid residues differing Piks‐1 from Pikm‐1 reveal that Piks‐E229Q derived from the exchange of Glu229 to Gln229 in Piks‐1 gains recognition specificity against AvrPik‐D but not AvrPik‐A or ‐E, indicating that Piks‐E229Q partially restores the Pikm spectrum. By contrast, Piks‐A261V derived from the exchange of Ala261 to Val261 in Piks‐1 retains Piks recognition specificity. We conclude that Glu229 in Piks‐1 is critical for Piks breaking the canonical Pik/AvrPik recognition pattern. Intriguingly, binding activity and ectopic cell death induction is maintained between Piks‐A261V and AvrPik‐D, implying that positive outcomes from ectopic assays might be insufficient to deduce its immune activity against the relevant effectors in rice and rice blast interaction.